Graphene-Based Nanomaterials for Dental Applications: Principles, Current Advances, and Future Outlook - Li, Xiaojing; Liang, Xin; Wang, Yanhui; Wang, Dashan; Teng, Minhua; Xu, Hao; Zhao, Baodong; Han, Lei (Frontiers in bioengineering and biotechnology, 2022)
With the development of nanotechnology, nanomaterials have been used in dental fields over the past years. Among them, graphene and its derivatives have attracted great attentions, owing to their excellent physicochemical property, morphology, biocompatibility, multi-differentiation activity, and antimicrobial activity. In our review, we summarized the recent progress about their applications on the dentistry. The synthesis methods, structures, and properties of graphene-based materials are discussed. Then, the dental applications of graphene-based materials are emphatically collected and described. Finally, the challenges and outlooks of graphene-based nanomaterials on the dental applications are discussed in this paper, aiming at inspiring more excellent studies.